Wenyang Huazhuo Tongluo formula, a Chinese herbal decoction, improves skin fibrosis by promoting apoptosis and inhibiting proliferation through down-regulation of survivin and cyclin D1 in systemic sclerosis. Issue 1 (December 2016) - Han, Li; Bian, Hua; Ouyang, Jingfeng; Bi, Yuefeng; Yang, Lei; Ye, Songshan
Abstract Background Fibrosis is a major contributor to systemic sclerosis (SSc)-related morbidity, and rapid, progressive skin involvement predicts later mortality. Western medicine therapies for SSc cannot produce satisfactory effects currently, while Traditional Chinese Medicine (TCM), such as the Wenyang Huazhuo Tongluo (WYHZTL) formula, a Chinese herbal decoction, has shown amazing anti-fibrosis efficacy on SSc in clinical applications. This study is aiming to investigate the anti-fibrotic mechanism of WYHZTL formula for the treatment of SSc. Methods Fibroblasts from primary culture of skin lesions of SSc patients were exposed to rat medicated sera containing WYHZTL or XAV939, a small-molecule inhibitor of both tankyrase 1/2 and Wnt/β-catenin pathway. Cell counting kit-8 assay and Annexin V FITC/PI apoptosis kit were used to analyze cell proliferation and apoptosis in fibroblasts, respectively. Reverse transcription-polymerase chain reaction (RT-PCR) and western blotting were used to detect the mRNA and protein levels of cyclin D1 and survivin. Results After 28, 48 and 72 h of incubation, the proliferative ability of the fibroblasts cells was obviously reduced by the sera containing WYHZTL compared with that in the control group; the percentage of apoptotic cell population in the sera containing WYHZTL treated fibroblasts cells was significantly higher than that in those treated with the control sera, and was about similar to that in those treated with XAV939. The sera containing WYHZTL could down-regulate both mRNA and protein levels of cyclin D1 and survivin, compared with the control group. Conclusions The present study demonstrates the antiproliferative and pro-apoptotic actions of WYHZTL formula against fibroblasts and the effect may be related to the down-regulation of mRNA and protein levels of cyclin D1 and survivin in SSc.